(untitled) (IIUC Business Review, 2026)
The concept of in-app purchase intention within the context of online games pertains to the probability of a game player to engage in the act of acquiring virtual products, currency, objects, or premium features within the game by using actual monetary resources. This research intends to fill the knowledge gap on game players’ continuation intentions and the antecedents that lead to in-app purchases in an emerging economy, Bangladesh in particular. The proposed framework of gamer’s intention to continue games and in-apps purchase intent has formed with the variables such as social influence, difficulty, game design quality, and escapism through structural equation modeling where 400 responses have been collected by using a seven-point Likert scale questionnaire. The collected data is coded and analyzed in AMOS 22 for final recommendations. These findings provide significant insights for game marketers seeking to succeed in Bangladesh’s gaming industry. Developers may better match players’ expectations through game design, marketing campaigns and increase in-app purchase revenue by gaining a deeper grasp of the factors that influence players’ intentions to continue playing a game. IIUC Business Review, Vol.-13, Issue-1, December 2024, pp. 9-32